Bench-to-bedside review: β(2)-Agonists and the acute respiratory distress syndrome - Perkins, Gavin D (BioMed Central, 2004)
The acute respiratory distress syndrome (ARDS) is a devastating constellation of clinical, radiological and pathological signs characterized by failure of gas exchange and refractory hypoxia. Despite nearly 30 years of research, no specific pharmacological therapy has yet proven to be efficacious in manipulating the pathophysiological processes that underlie this condition. Several in vitro and in vivo animal or human studies suggest a potential role for β(2)-agonists in the treatment of ARDS. These agents have been shown to reduce pulmonary neutrophil sequestration and activation, accelerate alveolar fluid clearance, enhance surfactant secretion, and modulate the inflammatory and coagulation cascades. They are also used widely in clinical practice and are well tolerated in critically ill patients. The present review examines the evidence supporting a role for β(2)-agonists as a specific pharmacological intervention in patients with ARDS.